2009
DOI: 10.1182/asheducation-2009.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and sickle cell disease: two distinct diseases or part of the same process?

Abstract: A physician diagnosis of asthma in children and adults with sickle cell disease (SCD) has been associated with increased rates of pain and acute chest syndrome (ACS) episodes and premature death. Despite the clinical significance of a doctor’s diagnosis of asthma in individuals with SCD, the criteria for a physician diagnosis of asthma are not well defined. Many features of asthma are common in individuals with SCD, including symptoms of wheezing, obstructive lung disease and airway hyper-responsiveness. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 59 publications
1
32
1
Order By: Relevance
“…The largest increase in treatment was attributed to the group started on both hematologic and respiratory medications. Studies on SCD children additionally diagnosed with asthma have suggested a beneficial role of treatment with albuterol and ICS [29][30][31][32][33][34][35]. In our study, approximately 35.9 % of the study population had a concurrent diagnosis of asthma, but an improvement in FEV1% of predicted was seen in all groups started on medications regardless of a concurrent diagnosis.…”
Section: Impact Of Medication Status Gv and Acsmentioning
confidence: 38%
“…The largest increase in treatment was attributed to the group started on both hematologic and respiratory medications. Studies on SCD children additionally diagnosed with asthma have suggested a beneficial role of treatment with albuterol and ICS [29][30][31][32][33][34][35]. In our study, approximately 35.9 % of the study population had a concurrent diagnosis of asthma, but an improvement in FEV1% of predicted was seen in all groups started on medications regardless of a concurrent diagnosis.…”
Section: Impact Of Medication Status Gv and Acsmentioning
confidence: 38%
“…The prevalence of asthma among pediatric patients with SCD appears to be similar to that in children of African descent in the general population (57,60). As mentioned earlier, obstructive lung disease in adults with SCD is less common, occurring in less than 3% of patients (56).…”
Section: Asthma/reactive Airways Diseasementioning
confidence: 65%
“…5 There is ample evidence that ''asthma'' is a commonly occurring comorbidity in children with sickle cell disease [6][7][8][9][10][11][12] with a reported prevalence varying from 2% to 45%. [6][7][8][9][10][11]13,14 However, it is not clear what respiratory characteristics in the child with sickle cell disease are appropriately attributed to underlying asthma as defined in the guidelines 15 as opposed to being caused by the pathology that contributes to sickle cell disease associated pulmonary dysfunction. 16 It is clear that those children with asthma or asthma-like symptoms are at increased risk of morbidity associated with higher rates of acute chest syndrome, vaso-occlusive events, stroke, pain, as well as death.…”
mentioning
confidence: 94%
“…15 The reader is referred to the guidelines for in depth coverage of these issues (www.nhlbi.nih.gov/ guidelines/asthma/index.htm). No prospective controlled trials evaluating drug treatments for asthma symptoms in patients who have both sickle cell disease and asthma have been published, 13,16,21 and there are certain caveats to consider when prescribing these medications to children with sickle cell disease that are described in this update.…”
mentioning
confidence: 97%